A comparative study of drinking water biofilm monitoring with flow cell and Propella (TM) bioreactors - Lúcia Chaves Simões (2012)
Monitoring of drinking water (DW) biofilm formation under different process conditions was performed using two distinct bioreactors: a Propella (TM) and a flow cell system. Biofilms were grown on polyvinyl chloride (PVC) and stainless steel (SS) coupons under laminar (Reynolds number: 2000) and turbulent (Reynolds number: 11000) flow. The parameters analysed were the numbers of total and cultivable bacteria. The impact of different process conditions was assessed after the biofilms reached steady-state. The number of total bacteria was mostly higher than those cultivable. Biofilm steady-state was achieved in 3 days in both bioreactors with adhesion surfaces under turbulent flow. Under laminar flow it was only achieved in 6 days. The numbers of total and cultivable bacteria in turbulent flow-generated biofilms were similar in both bioreactors, regardless of the adhesion surface tested. Under laminar flow, the Propella (TM) bioreactor allowed the formation of steady-state biofilms with a higher number of total and cultivable bacteria than the flow cell system. Comparing the effects of the flow regime on biofilm accumulation, only turbulent flow-generated biofilms formed on the flow cell system had a higher amount of total and cultivable bacteria than those formed under laminar flow. In terms of adhesion surface effects, a higher number of total and cultivable cells were found on PVC surfaces compared to SS when biofilms were formed in the flow cell system. Biofilm formation on PVC and SS was similar in the PropellaTM system for both flow regimes.